Use of Electronic Information Resources: a Study of ADESH Institute of Engineering and Technology, Faridkot, Punjab, India - Maan, Inderjeet Singh (Journal of Information and Knowledge, 2013)
The electronic information resources are gaining more and more attention of library users and becoming an integral part of every library collection. Among other characteristics of electronic information resources, full text and online access; make them able to hold a pertinent place in the library collection. They are playing a vital role in enhancing the modern research and development activities. Most of the content providers are now actively participating in this digital information resource revolution. It is important to know to what extent these electronic resources are used by the end users. The present study is an effort to know the various purposes of use of electronic information resources. The users were also asked answer the question; whether use of electronic information resources have impacted on the performance of their academic work or not?